2016
DOI: 10.5430/rwe.v7n2p1
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate Change on Agricultural Trade in the MENA Region

Abstract: Human-induced climate change has been one of the most widely discussed issues of scientific and political spheres in the recent decades, and it has been overwhelmingly agreed that climate change poses a very serious threat for the environment and the economy. It has been observed that increasing temperatures and extremities in weather patterns create a serious challenge for agriculture and food security especially in various disadvantaged regions. Even in the most optimistic scenarios, where global mean temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In other words, the results have proven that climate change is threating agricultural trade flows in the region such that the region may continue to be a net-food importer. The results corroborate those of Tekce and Deniz [15], Khan et al [17], Adesete et al [25], Fusco [27], Baptista et al [11], Affoh et al [24], Brenton et al [2] and Dumortier et al [1] who in their respective studies also found negative impacts of climate change on agricultural trade.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In other words, the results have proven that climate change is threating agricultural trade flows in the region such that the region may continue to be a net-food importer. The results corroborate those of Tekce and Deniz [15], Khan et al [17], Adesete et al [25], Fusco [27], Baptista et al [11], Affoh et al [24], Brenton et al [2] and Dumortier et al [1] who in their respective studies also found negative impacts of climate change on agricultural trade.…”
Section: Resultssupporting
confidence: 86%
“…banks on lagged variables as instruments. The research aimed to estimate the following dynamic panel econometric models developed basing on specifications of Tekce and Deniz [15], Mahrous [23] and Affoh et al [24]. The logarithmic function was employed so that the estimates can be interpreted as elasticities and to reduce problems of non-normality [21].…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient (−0.07) of TRO shows that a 1% increase in economic growth leads to an 0.07% diminish in AEP in the long run. According to Tekce and Deniz, (2016), agricultural trade is among the most vulnerable areas of the economy that climate change is projected to disrupt, particularly in developing countries [67]. Evidence from Tian et al, (2018) cohort studies concluded that economic growth and international trade have a clear impact on the environment and its resources.…”
Section: Long-run and Short-run Elasticitiesmentioning
confidence: 99%
“…To revise these trends, Southern African countries need to ght climate change so as to improve agricultural productivity and boost agricultural exports (Fox and Jayne, 2020). Previous empirical studies have cited negative effects of climate change on agricultural trade ows (Tekce and Deniz, 2016;Egbendewe et al, 2017;Khan et al, 2019;Adams et al, 2021). However, compared to the available literature, there are few empirical studies on climate change impacts on agricultural trade and food security.…”
Section: Introductionmentioning
confidence: 99%